2021
DOI: 10.1093/database/baab032
|View full text |Cite
|
Sign up to set email alerts
|

MetamORF: a repository of unique short open reading frames identified by both experimental and computational approaches for gene and metagene analyses

Abstract: The development of high-throughput technologies revealed the existence of non-canonical short open reading frames (sORFs) on most eukaryotic ribonucleic acids. They are ubiquitous genetic elements conserved across species and suspected to be involved in numerous cellular processes. MetamORF (https://metamorf.hb.univ-amu.fr/) aims to provide a repository of unique sORFs identified in the human and mouse genomes with both experimental and computational approaches. By gathering publicly available sORF data, norma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 60 publications
0
21
0
Order By: Relevance
“…As recent studies found that some putative lncRNAs contain a short open reading frame (sORF) [35], we further analyzed the association of lncRNAs and sORF using the explanation results of Xlnc1DCNN. Some false negative sequences were randomly selected and checked if they contained sORF by using MetamORF [36]. While MetamORF found sORFs in some of these sequences, the reported regions of these sORFs did not correspond to the important regions highlighted by the explanation results.…”
Section: Discussionmentioning
confidence: 99%
“…As recent studies found that some putative lncRNAs contain a short open reading frame (sORF) [35], we further analyzed the association of lncRNAs and sORF using the explanation results of Xlnc1DCNN. Some false negative sequences were randomly selected and checked if they contained sORF by using MetamORF [36]. While MetamORF found sORFs in some of these sequences, the reported regions of these sORFs did not correspond to the important regions highlighted by the explanation results.…”
Section: Discussionmentioning
confidence: 99%
“…RibORF was used to systematically detect the actively translated regions in the Ribo-seq datasets ( 37 ). Moreover, the predicted ORFs from MetamORF ( 38 ) and OpenProt ( 39 ) were obtained. The ORFs predicted by at least two methods were remained for further analyses.…”
Section: Methodsmentioning
confidence: 99%
“…For detailed query, sORFs.org incorporates a Biomart function, where one can tailor the search for microproteins by customising their queries according to species, chromosome number, start codons and sORFs attributes [ 14 ]. On the other hand, MetamORF is more limited in the sense that it only contains sORF data from Homo sapiens and Mus musculus , but its data has been experimentally and computationally verified, where one can browse the database according to gene locus, ORF, and transcript [ 110 ]. For OpenProt, since it is a large database, sORFs are stored under the heading of altORFs, where there is annotation of sORFs within ncRNA and pseudogene transcripts, hence some data downloaded from OpenProt in FASTA files may contain sequences longer than 100 codons [ 111 , 112 ].…”
Section: Microprotein Databasesmentioning
confidence: 99%